Merchant Moscow : images of Russia's vanished bourgeoisie - West, James L., 1944-; Petrov, I͡U. A. (I͡Uriĭ Aleksandrovich), 1955- (Princeton University Press, 1998)
With the collapse of the Soviet system, the long-neglected history of the early capitalists is being recovered and rewritten. Once regarded as the "losers" in the Russian Revolution, these merchants can now be seen as early pioneers in Russia's transformation to a free market economy. This book is the first joint Russian-American collaborative project on the history of Russian entrepreneurship. Merchant Moscow puts a human face on early Russian capitalism. It presents thematic groupings of historic photographs paired with commentaries by contemporary Russian and American historians. The pictures provide a stunning, wide-ranging visual portrait of Imperial Russia's most influential entrepreneurial elite, the Moscow merchantry, while the accompanying articles interpret the photographs and place them in the larger cultural context of prerevolutionary Russia. Here is a surprising new view of the bourgeoisie during the Silver Age, revealed for the first time in this fascinating volume. The fourteen contributing historians selected and ordered photographs that best illustrate their specialized knowledge of the period. They have framed their topics in a variety of ways. Some have chosen to pursue traditional topics, such as collective biography, institutional history, or the history of business practices. Others have approached the photographs in more experimental ways, emphasizing the semiotics of dress, discourses of identity, or the history of daily life. Together they offer fresh perspectives on the successes and failures of Russia's first experiment with entrepreneurial capitalism. Originally published in 1998. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.